Pengaruh Self Leadership Terhadap Performa Mahasiswa Universitas Riau dengan Gamiification Sebagai Variabel Pemoderasi - Rahmat Junaidi; Maha Martabar Mangatas Lumbanraja; Sri Wahyuni Wildah (Forum Kerjasama Pendidikan Tinggi, 2022)
Performance or performance is a concept and theory which by a number of academics has become a topic that is continuously studied with the aim of being able to find the most appropriate alternative to the obstacles that arise. Based on the results of the initial search, it was found that the leadership factor is a variable that is often used as a cause of performance improvement, while the self-leadership variable is a factor that will be investigated in 2021. The researcher also found that regulatory factors and rewards for achievements are similar to the concept of a known game. in Gamification theory is a factor that strengthens (and is translated as a moderating factor) the influence between self-leadership and student performance. This research is a quantitative study using the SEM-PLS analysis technique on primary data in the form of a questionnaire instrument which was distributed to 97 samples representing the student population of the University of Riau. The results showed that the variable value increase in the self-leadership variable had a significant impact on increasing student performance scores, and this was positively moderated (reinforced) by the increasing level of gamification carried out by the university environment.